Analisis Hukum Pernikahan Muḥallil Terhadap Interaksi Sosial Janda Cerai di Masyarakat - J, Jumadiah; S, Sutriani; H, Hamdani; Saifullah, T (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out about Muhallil’s marriage from a social perspective, and the bad views towards his ex-wife. The approach used is normative. Data collection is prioritized on primary, secondary and tertiary sources of legal material, in the form of legal theories. Such as the Koran, Hadith, and fiqh books. The results of the research show that scholars differ in their views on muhalill. There are scholars who allow it on condition that the marriage is sincere, not to be divorced later, has had husband and wife relations, and so on. There are also scholars who do not allow muhalillil for any reason because the aim is to make marriage legal for their ex-husband, but if you look at social interactions in society towards divorcees, this is a normal thing, if a couple is no longer compatible, resulting in divorce or the status of a divorcee. Is not a taboo matter, but divorcees who have been triple divorced are talked about in society and ridiculed. The results of the review of people’s lives show that there are obstacles faced after living as a divorcee, especially after three divorces, resulting in difficulty doing one’s own work, difficulty raising one’s own children, difficulty meeting economic needs, experiencing feelings of discomfort towards status as a divorcee.